T-odd correlations in B±→D*K*± decays - Kovalchuk, V.A. (Вопросы атомной науки и техники, 2007)
We examine T violating triple product correlations in the processes B±→D* K*±, D*→Dπ⁰, Dγ, D→f, where the neutral D(D*) meson is a superposition of D⁰(D*⁰) and D⁰(D*⁰). It is shown that large T violating asymmetries (~18% for the weak phase γ = 62°) are possible within the Standard Model for hadronic final states `f’ such that D⁰→f is doubly Cabibbo suppressed mode while D⁰→f is Cabibbo allowed mode.